Differential proteomic expression in indolent versus transforming oral lichen planus. Issue 4 (10th January 2023) - Xie, Fangyi; Gleue, Casey A.; Deschaine, Maria; Dasari, Surendra; Sartori‐Valinotti, Julio C.; Charlesworth, M. Cristine; Meves, Alexander; Lehman, Julia S.
Abstract: Oral lichen planus (OLP) confers an approximately 1% risk of transformation to oral squamous cell carcinoma (OSCC). Early identification of high‐risk OLP would be very helpful for optimal patient management. We aimed to discover specific tissue‐based protein biomarkers in patients with OLP who developed OSCC compared to those who did not. We used laser capture microdissection– and nanoLC–tandem mass spectrometry to assess protein expression in fixed lesional mucosal specimens in patients with indolent OLP (no OSCC after at least 5‐year follow‐up, n = 6), transforming OLP (non‐dysplastic epithelium with lichenoid inflammation marginal to OSCC, n = 6) or normal oral mucosa (NOM, n = 5). Transforming OLP protein profile was enriched for actin cytoskeleton, mitochondrial dysfunction and oxidative phosphorylation pathways. CA1, TNNT3, SYNM and MB were overexpressed, and FBLN1 was underexpressed in transforming OLP compared with indolent OLP. Integrin signalling and antigen presentation pathways were enriched in both indolent and transforming OLP compared with NOM. This proteomic study provides potential biomarkers, such as CA1 overexpression, for higher‐risk OLP. While further validation studies are needed, we propose that epithelial–mesenchymal transition may be involved in OLP carcinogenesis.